PERLUASAN METODE NEWTON DENGAN PENDEKATAN PARABOLIK - Rahman, Abdul; Putra, Supriadi; ', Bustami (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses the extension of Newton’s method derived from the Taylor expansion, where the curve is approached by a tangent line of the parabola. Analytically, it is shown that the iterative method has the cubic order of convergence, so it is more effective than the Newton’s method. Furthermore, computational results show that the iterative method is superior to the comparison methods in term of the number of iterations to obtain the estimated roots.